BERPIHAK PADA YANG MISKIN MELALUI GERAKAN MENANAM DAN MERAWAT SUMBER AIR: SEBUAH BENTUK PASTORAL EKOLOGI DI PAROKI BATURETNO – WONOGIRI – JAWA TENGAH - Hugo Bayu Hadibowo (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2021)
Water is a life’s symbol. Lack of water means loosing hope and life for the future. Nowadays, water’s scarcity is caused by deforesting. Environmental crisis causes some effect for human life, especially fresh water’s sustainability. Therefore, environmental crisis can be reflected based on human being’s experience facing many good creatures. Planting trees, such as Ficus benjamina, or known as weeping fig trees which held by Baturetno Parish, Wonogiri, Central Java, is one of the example how to reflect, respond, and care for our common home, our mother earth. There are some points that will be achieved through this programs such as reconciliation with nature, solidarity with the poor, and making collaborations in the context of dialogue. This environmental crisis is connected to human beeing’s relation with nature and God, even others. If the relationship between human being and God is broken, which caused by greed and self-centeredness minded we cannot live in harmony. Furthermore, I am trying to do a theological reflection according to Christiana Z. Peppard’s paradigm about “just water” and participation to take care of the earth. On the other hand, Laudato Si will complete this interpretation by inviting human being and institutions to make a self-conversion as a responsibility to take care of our common home. Pope Francis emphasized the commitment to proclaim the Good news through the actions. For God’s creation is a part of the Good news. These paradigms finally are able to be an instrument to make a theological reflection on planting movement in the context of Baturetno Parish.